Satisfaction of Financial Institution Staff Towards Staff Housing Loan: A Case Study - Md Yusof, Zahayu; Mansor, Rosnalini; Zaini, Bahtiar Jamili; Hui Chee, Lim (Management Research Journal, 2020)
Loan can be defined as money advanced to the borrower by the lender and obligated to pay back or repaid at a future time. Some of the company provided loan to its own staff. There are many pros and cons about this loan. Thus, we are interested on the factors that influence staff to use the staff housing loan. This study was conducted to identify the satisfaction level of financial institution’s staff towards staff housing loan and also to identify the relationship between the service quality, interest rate, repayment period and margin of finance that will affect staffs’ satisfaction towards staff housing loan of a financial institution in Malaysia. There are two stages of cluster sampling was used to collect the data and from sample of 197 staffs and later analyzed using statistical software namely, Statistical Package for Social Science (SPSS) and Analysis of Moment Structure (AMOS). Confirmatory Factor Analysis (CFA) together with Structural Equation Modeling (SEM) approach was used both to identify the significant direct influence on satisfaction among financial staff. As a conclusion, there is a high satisfaction level of financial institution staffs towards staff housing loan. Besides, service quality, interest rate and repayment period has positive relationship with staffs’ satisfaction towards staff housing loan. The result also shows that interest rate is the most significant factor that will affect staffs’ satisfaction towards staff housing loan.